Anticancer effect of Moringa oleifera in oral squamous cell carcinoma: a systematic review - Chandini Rajkumar; Saranya Ramsridhar; Vishnu Priya Veeraraghavan; Arul Prakash Francis; M. Purushotham; Uma Mageshwari (Discover Oncology)
Abstract Background and objective Oral squamous cell carcinoma is the most common form of mouth cancer. As plant-based medicines become increasingly popular, Moringa oleifera has been studied extensively for its plant-based components, and health benefits. The present review examined the anticancer effects of Moringa oleifera extracts on Oral squamous cell carcinoma. Materials and methods The study complied with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses standards. A comprehensive search was performed on PubMed, Scopus, and Google Scholar to find research papers published from January 2015 to August 2024 that assessed the effects of extracts of various parts of Moringa oleifera in Oral squamous cell carcinoma. Two independent reviewers separately assessed research study titles, abstracts, and the chosen full-text papers. The risk of bias in non-randomized exposure studies was classified as low, with some concerns high and extremely high. Results The final review yielded four in-vitro investigations, two molecular analyses, and five animal models. The study revealed that Moringa oleifera plant components have antioxidant, anti-inflammatory, anticancer, and chemo-preventive properties. All the 11 studies showed a low risk of bias. Conclusion The studies reviewed herein reveal that Moringa oleifera plant components have antioxidant, anti-inflammatory, anticancer, and chemopreventive properties. Although more clinical trials are needed to fully establish its efficacy and safety as a complementary therapy, the growing body of evidence positions Moringa oleifera as a promising natural adjunct to cancer treatment strategies.